The application of a medium-chain fatty diet and enteral nutrition in post-operative chylous leakage: analysis of 63 patients - Wang, Ke; Xiao, Jiaming; Li, Li; Li, Xu; Yang, Yilun; Liu, Zhiyu; Jiang, Jing (Frontiers in Nutrition, 2023)
Background: Postoperative chylous leakage (CL) is the pathologic leakage of chylomicron fluid after surgery. This retrospective study was performed to evaluate a uniform oral nutrition management strategy on the postoperative CL. Methods: We retrospectively reviewed patients who developed postoperative CL and received consultation from a clinical nutritionist in six departments of the Second Affiliated Hospital of Dalian Medical University from May 2020 to April 2022. We designed the oral nutrition intervention program which mainly standardized the type and amount of foods contained in the medium-chain acid diet (MCT-diet). The influencing factors of curative efficacy were analyzed. Finally, Binary logistic regression analysis was conducted to observe the relationship between curative efficacy and potentially predictive variables, including postoperative albumin, postoperative hemoglobin, surgical procedure, and drainage volume at consultation. Results: 63 patients with postoperative CL were included in this analysis. Of this number, 58 patients were cured successfully without other treatment. Three patients had a significantly prolonged recovery period, and the remaining two cases were treated by reoperation therapy. The leakage volume at the initiation of enteral intervention had no statistically significant difference in six surgical departments and surgical sites (left, right, median, and bilateral). The length of stay (LOS) of patients with CL after intervention was not significantly increased in cardiac, hepatobiliary, gastrointestinal, and urological surgeries. Patients with CL had longer LOS than those without CL in gynecology (P=0.044) and thyroid surgery departments (P=0.008). Each unit increase in postoperative hemoglobin would increase the probability of an effective outcome by 8%, which was statistically significant (P = 0.037). Conclusion: In treating patients with postoperative CL, we recommend MCT-diet and EN as the first option, rather than fasting, parenteral nutrition (PN), or octreotide.